1995
DOI: 10.1136/hrt.74.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular thrombi in a patient with the antiphospholipid syndrome.

Abstract: Echocardiographic four chamber view showing thrombi in the left ventricle (LV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Similar case reports of intracardiac thrombi have been reported. 4,5 Premature ischaemic heart disease may occur as in our patient; however, the role of anticardiolipin antibodies in this condition is not clear. 6 This documented case of 90% thrombosis of the right subclavian artery and 50% occlusion of both common carotids in the presence of antiphospholipid antibodies fulfils the Sydney criteria for APS diagnosis, which require the presence of at least one of the clinical criteria (Vascular thrombosis and/or pregnancy morbidity) and at least one of the laboratory criteria (Detection of lupus anticoagulant, anticardiolipin or anti-beta-2-glycoprotein 1 antibodies).…”
Section: Discussionmentioning
confidence: 66%
“…Similar case reports of intracardiac thrombi have been reported. 4,5 Premature ischaemic heart disease may occur as in our patient; however, the role of anticardiolipin antibodies in this condition is not clear. 6 This documented case of 90% thrombosis of the right subclavian artery and 50% occlusion of both common carotids in the presence of antiphospholipid antibodies fulfils the Sydney criteria for APS diagnosis, which require the presence of at least one of the clinical criteria (Vascular thrombosis and/or pregnancy morbidity) and at least one of the laboratory criteria (Detection of lupus anticoagulant, anticardiolipin or anti-beta-2-glycoprotein 1 antibodies).…”
Section: Discussionmentioning
confidence: 66%
“…Recently, ventricular thrombosis, right or left, has been documented in association with raised titres of anticardiolipid antibodies of the antiphospholipid group of connective tissue disorders [1,9]. However, to the best of our knowledge, none of those presented with thrombosis of the cardiac veins and/or their tributaries.…”
Section: Discussionmentioning
confidence: 87%
“…17 The efficacy of anticoagulant therapy on vegetative lesions is controversial; [11][12][13][14][15][16] some authors have suggested that vascular proliferation, infiltration of fibroblasts, necrosis and calcification are the predominate factors involved in the etiopathogenesis of echogenic masses on the left heart valves in patients with APS, 11,15 and would therefore not be expected to respond to fibrinolytic and anticoagulant therapies, whereas others have reported success in treating these vegetations with anticoagulant therapy. [12][13][14] In addition to the studies of valvular lesions, mural endocardial thrombi have been documented in patients with APS, [1][2][3][4][5][6][7] in some cases, on normal-functioning right and left ventricles. 4,7 There have been few reports of thrombus on the tricuspid valve in patients with APS; Day et al reported a right atrial thrombi associated with PAPS, one of which was adherent to the edge of the anterior leaflet of the tricuspid valve.…”
Section: Discussionmentioning
confidence: 99%